Acetaminophen metabolism revisited using non-targeted analyses: Implications for human biomonitoring. (April 2021) - David, Arthur; Chaker, Jade; Léger, Thibaut; Al-Salhi, Raghad; Dalgaard, Marlene D.; Styrishave, Bjarne; Bury, Daniel; Koch, Holger M.; Jégou, Bernard; Kristensen, David M.
Highlights: Non-targeted HRMS method identified overlooked acetaminophen metabolites in human. Thiomethyl metabolites showed delayed appearance with peak time at 24 h in plasma and urine. The conjugated thiomethyl metabolites are produced via the thiomethyl shunt pathway. Thiomethyl metabolites are of comparable diagnostic sensitivity compared to other metabolites. Thiomethyl metabolites could extend the window of exposure assessment for APAP use. Abstract: The analgesic paracetamol/acetaminophen (N-acetyl-4-aminophenol, APAP) is commonly used to relieve pain, fever and malaise. While sales have increased worldwide, a growing body of experimental and epidemiological evidence has suggested APAP as a possible risk factor for various health disorders in humans. To perform internal exposure-based risk assessment, the use of accurate and optimized biomonitoring methods is critical. However, retrospectively assessing pharmaceutical use of APAP in humans is challenging because of its short half-life. The objective of this study was to address the key issue of potential underestimation of APAP use using current standard analytical methods based on urinary analyses of free APAP and its phase II conjugates. The question we address is whether investigating additional metabolites than direct phase II conjugates could improve the monitoring of APAP. Using non-targeted analyses based on high-resolution mass spectrometry, we identified, in a controlled longitudinal exposure study with male volunteers, overlooked APAP metabolites with delayed formation and excretion rates. We postulate that these metabolites are formed via the thiomethyl shunt after the enterohepatic circulation as already observed in rodents. Importantly, these conjugated thiomethyl metabolites were (i) of comparable diagnostic sensitivity as the free APAP and its phase II conjugates detected by current methods; (ii) had delayed peak levels in blood and urine compared to other APAP metabolites and therefore potentially extend the window of exposure assessment; and (iii) provide relevant information regarding metabolic pathways of interest from a toxicological point of view. Including these metabolites in future APAP biomonitoring methods therefore provides an option to decrease potential underestimation of APAP use. Moreover, our data challenge the notion that the standard methods in biomonitoring based exclusively on the parent compound and its phase II metabolites are adequate for human biomonitoring of a non-persistent chemical such as APAP.